Experimental research on noninvasive reconstruction of optical parameter fields based on transient radiative transfer equation for diagnosis applications. (January 2019) - Qi, Hong; Zhao, Fang-Zhou; Ren, Ya-Tao; Qiao, Yao-Bin; Wei, Lin-Yang; Islam, Md Arafat; Ruan, Li-Ming
Highlights: Noninvasive reconstruction of optical parameter fields is investigated experimentally. An SQP scheme based on Gaussian Markov random field is developed. The reconstruction method is proved to be accurate and efficient experimentally. Abstract: The noninvasive reconstruction of optical parameter fields in participating phantom is investigated experimentally based on the measured time-resolved radiative signals, which are detected by the time-correlated single-photon counting system. The discrete ordinate method is employed to solve the forward transient radiative transfer equation to simulate the time-resolved radiative transfer in the physical phantom exposed to ultra-short pulse laser irradiation. On top of that, the sequential quadratic programming algorithm based on the generalized Gaussian Markov random field is applied to solve the inverse problem. To improve the computational efficiency, an adjoint equation technique is adopted to determine the gradient of objective function. Good agreement was obtained between the predicted optical parameter fields and realistic ones. All the reconstruction results demonstrate that the proposed reconstruction methods are proved to be accurate and efficient experimentally.